The Dispute Regarding the Role of Analogy in the Natural (Rational) Affirmation of God’s Existence and the Definement of His Nature - Kazimierz Gryżenia (Studia Gilsoniana)
At the beginning of the article, I speak of two ways of reflecting on God: natural and revealed theology. It is a disadvantage that two of them are often pitted against each other. I demonstrate their complementarity, with a focus on the abilities to research natural theology, that is, the philosophy of God. Next is analogy’s part in the cognition of God. Here, there are two issues to consider: finding proof of God’s existence and describing his nature. Most authors believe that analogy plays a part only in describing God’s nature and speak for the analogy of attribution. Demonstrating the existence of God is generally not addressed, taking the fact of God’s existence as already granted. Therefore, analogy ceases to be a focus. However, representatives of realist philosophy, existential Thomism, hold a different belief. They state that analogy can, and should, be applied in the argumentation for the existence of God and for describing His nature. The only problem that still exists is choosing which type of analogy to administer. This very analogy is the analogy of transcendental proportionality. It has been thought of, and is in fact possible, only on the basis of the existential conception of being, which is to be found in the views of St. Thomas Aquinas. It is similar in its structure to the analogy of attribution, as in both there is a primary analogate and secondary analogate. However, its primary analogate is radically differently understood than in the analogy of attribution.